Exploring the Difficulties Encountered by the Non-English Department Students in Learning the English Language: A Study on the Tertiary Level of Education in Bangladesh (Global Journal of Human-Social Science, 2021)
Most of the non-English departments at the tertiary level of education in Bangladesh conduct the English language course for the development of English language skills of the non-English department students. However, the non-English department students at the tertiary level of education in Bangladesh face many troubles in learning the English language efficiently. The purpose of this study was to explore the difficulties encountered by the non-English department students at the tertiary level of education in Bangladesh in learning the English language. This study followed a quantitative research approach. Data collected from 100 non-English department students both from public and private universities of Bangladesh through survey questionnaires and semi-structured interviews. The findings of this study disclosed that the non-English department students face the most difficulty in productive skills (speaking and writing). Moreover, duration of the class and semester, syllabus design, needs analysis, classroom techniques, and methods are the significant factors that affect the English language learning of the non-English department students.
Keywords: non-english department; quantitative; tertiary level; Bangladesh